2015
DOI: 10.1002/path.4535
|View full text |Cite
|
Sign up to set email alerts
|

SCD5‐induced oleic acid production reduces melanoma malignancy by intracellular retention of SPARC and cathepsin B

Abstract: A proper balance between saturated and unsaturated fatty acids (FAs) is required for maintaining cell homeostasis. The increased demand of FAs to assemble the plasma membranes of continuously dividing cancer cells might unbalance this ratio and critically affect tumour outgrowth. We unveiled the role of the stearoyl-CoA desaturase SCD5 in converting saturated FAs into mono-unsaturated FAs during melanoma progression. SCD5 is down-regulated in advanced melanoma and its restored expression significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Its expression is downregulated during tumor progression and related to the epithelial-mesenchymal transition reverted process [13]. SCD5 expression is associated with the reduction of intracellular pH, vesicle movement, and pro-tumoral protein secretion [19]. It has also been described that miR-221 and miR-222 have a negative feedback connection to SCD5 expression [13].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…Its expression is downregulated during tumor progression and related to the epithelial-mesenchymal transition reverted process [13]. SCD5 expression is associated with the reduction of intracellular pH, vesicle movement, and pro-tumoral protein secretion [19]. It has also been described that miR-221 and miR-222 have a negative feedback connection to SCD5 expression [13].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…The growing evidence for a prominent role of lipids in tumor growth, together with the fact that human SCD-1, and more recently also SCD-5, have been found expressed and associated with the malignancy of the disease [31,42], prompted us to analyze if the expression of c-Myc correlates with increased levels of SCD-1 or SCD-5 in tumors with higher prognosis of tumorigenesis. Since SCD-1 protein is increased in prostate tumors [31], we decided to analyze whether c-Myc and SCD-1 proteins are co-expressed in histological tumor samples from patients and control tissues using immunofluorescence assays.…”
Section: Resultsmentioning
confidence: 99%
“…Cell homeostasis is highly associated with the balance between saturated and unsaturated FAs. The continuously dividing tumor cells need a large amount of FAs to assemble their plasma membranes; this may disrupt the ratio and assist tumor growth . However, previous studies have suggested that stearoyl‐CoA desaturase 5 (SCD5) reduces the aggressiveness of UVM .…”
Section: Discussionmentioning
confidence: 99%
“…33 However, previous studies have suggested that stearoyl-CoA desaturase 5 (SCD5) reduces the aggressiveness of UVM. 33,34 Further research is needed to verify this.…”
Section: Discussionmentioning
confidence: 99%